Potensi Sumberdaya Lamun Untuk Mendukung Pengembangan Wisata Di Pantai Mengiat Nusa Dua, Bali - Wandiani, Ida Ayu Novera; Restu, I Wayan; Pratiwi, Made Ayu (Journal of Marine and Aquatic Sciences; Vol 6 No 1 (2020)DO - 10.24843/jmas.2020.v06.i01.p10, 2020)
Seagrasses have functions and roles as primary producers, biota habitats, bottom seawater stabilizers, sediment catchers, and nutrient recyclers. With the function of seagrass as a habitat of biota, it can provide economic opportunities to be utilized as a marine tourism, especially marine ecotourism. Marine ecotourism is a concept of sustainable use of coastal resources with environmental service system that prioritizes coastal natural resources as an object of service. This study aimed to identify the seagrass potency ecologically and socially and to formulate the seagrass management strategies to support tourism development in Nusa Dua. This study was conducted from January-March 2017 using observation and interview method. Observation method was used to define the condition of seagrass, fish species, and environmental parameters. Then Interview method was used to know social conditiion of Mengiat Beach and analyzed by SWOT to formulate the seagrass management strategies.  The result showed, there were 6 species, i.e ., Halophila ovalis, Cymodocea Halodule pinifolia rotundata, Syringodium isoetifolium, Thalassia hemprichii, and Thalassodendron ciliatum . The percentage of seagrass coverage at 5 stations tend to be low (5,639%-47,49%). Based on Tourism Suitability Indexes, Mengiat Beach in Nusa Dua is suitable (S2) for tourism activities with value 75,08%. The priority strategies are formulated from the SWOT matrix is applying under water garden in seagrass base on tourism planning.